Effects of LiCF3SO3 on PVDF-HFP/MG49 (70/30) based blend polymer electrolyte - Ataollahi N.; Ahmad A.; Hamzah H.H.; Rahman M.Y.; Mohamed N.S. (2023)
Poly (vinylidene fluoride-hexafluoro propylene) (PVDF-HFP), Poly (methyl methacrylate)-grafted natural rubber (MG49) (70/30) complexed with different compositions of lithium trifluoromethane sulfonate (LiCF3SO3) based solid polymer electrolyte has been prepared using solution casting method. This work has demonstrated that conductivity values were found to depend upon the concentration of LiCF3SO3. The highest ionic conductivity was 1.9710-4 S cm-1at 25 wt. % of LiCF3SO3 at room temperature. X-ray diffraction (XRD) indicates decrease in the degree of crystallinity by increasing of salt concentration. (2013) Trans Tech Publications, Switzerland.